Analisis Pengendalian Kualitas Barang Masuk Produk Cacat Berdasarkan Data Non-Conformance Report Menggunakan Metode Six Sigma di PT.XYZ - Mawarni, Iga (Universitas PGRI Semarang, 2026)
PT. XYZ is a manufacturing company established in Indonesia since 1981. The product that is the focus of this study is the Center Plate. The main problem faced by the company lies in the high number of defective goods entering the production line, thereby hindering the smooth running of the production process. To overcome this, this study applies the Six Sigma method to analyze the causes of the problem and provide recommendations for improvement in the quality of the Center Plate. Based on the analysis results, two types of defects were found, namely visual defects and dimensional defects. Through the Six Sigma approach, a sigma level value of 4.059 was obtained, with the main contributing factors being machinery, labor, and environmental conditions.